Interactions between eukaryotic and prokaryotic microorganisms in activated sludge: a molecular approach to improve wastewater treatment - Neto, Marta Martins (2010)
Wastewater treatment is one of the most important biotechnological processes which are used worldwide to treat municipal and industrial sewage. Activated-sludge processes aim to achieve a maximal reduction of the Biological Oxygen Demand (BOD) of wastewater with a minimal production of biological solids. Even though many microbiological methods are available to study the activated sludge communities, many recent questions on the role of certain microorganisms are kept unanswered. A crucial addressed by the present work is to know if the presence of different groups of bacteria and protozoa lead to significant consequences on the process performance. Focusing on the importance of the interactions between the prokaryotic and the eukaryotic populations, the work will contribute to the knowledge of how microbial communities are established in a complex environment as the activated sludge processes.